Implementation of the Trader Role Play Method to Improve the Social and Emotional Abilities of Early Childhood - Arif Nursihah; Heri Hidayat; Devy Oktaviany; Indah Sari Dewi. Z (Universitas Al-Hikmah Indonesia, 2026)
Early childhood education contributes significantly to building the foundation of children's abilities, including social-emotional skills, which are the foundation that will foster a sense of security, the ability to socialize, communicate, and share with friends. However, observations show that most children aged 5-6 years still fight over toys, hit friends, get angry easily, and like to give orders. The purpose of this study is to improve social-emotional skills through the application of the trader role-play method. This study uses the classroom action research (CAR) model from Kemmis & Mc Taggart which was implemented in two cycles on 21 children in group B Raudhatul Athfal. Data collection was carried out through observation, performance assessment, interviews and documentation, then analyzed qualitatively with triangulation of techniques and sources. The results of the study showed an increase in social-emotional skills. In the first cycle, the majority of children were in the